How to Conduct CSR Activities to Build Consumer Trust and Corporate Reputation in Covid-19 Pandemic? - Thao Thi Phuong Nguyen; Anh Van Nguyen (Asian Academy of Management Journal, 2024)
The world has changed dramatically since the emergence of the coronavirus disease 2019 (Covid-19) pandemic. This crisis has put companies under the test for their commitment to moral business conduct and corporate social responsibility (CSR). Facing the challenges for survival as well as financial strains could push firms with difficult choices in their CSR practices. The aim of this study is to explore the impact of CSR activities in building customer trust and company reputation with limited resources in the Covid-19 pandemic context. The paper collected data on latent constructs through a survey of 494 consumers by convenience sample in Vietnam. Confirmatory factor analysis assessed psychometric properties of the constructs, while the structural equation modeling (SEM) technique was used to examine posited hypotheses. The results show that economic responsibility has a positive impact on expertise trust; legal responsibility and ethical responsibility positively impact integrity trust; philanthropic responsibility has a positive effect on social benevolence trust. However, only ethical responsibility and philanthropic responsibility can directly influence corporate reputation. In addition, three dimensions of trust strengthen the link between CSR initiatives and company reputation. Among them, social benevolence trust plays the most critical role in creating a reputation. Based on this finding, some management implications are also discussed regarding how corporations can allocate appropriate resources for different CSR activities so that they could leverage benefits from CSR strategy in their business. Moreover, the results obtained open future lines of comparative research on the impact of CSR practices, mediated by trust in corporate reputation, between countries with different cultures and religious beliefs.